Willingness to pay for the control of water hyacinth in an urban environment of South Africa - Law, Matthew Charles (Rhodes University, Faculty of Commerce, Department of Economics, 2008)
Water hyacinth is recognised as one of the most problematic invasive aquatic plant species in Africa. For this reason considerable funds are spent each year on itscontrol. As a consequence of the amount of money being spent on problems such as the invasion of water hyacinth, and because of the recognition of the ongoing and accelerated efforts that are required in the future, recent research has focused on accurately quantifying the costs and benefits of control of invasive species to aid policy decisions.A comprehensive cost-benefit analysis would be able to identify if the funds are justified and are being spent effectively. This thesis provides an example of a cost-benefit analysis of funds spent on the control of water hyacinth in an urban environment in South Africa. In order to develop a comprehensive assessment of the total economic value of the control of water hyacinth to an urban population, the Nahoon River in East London was selected as the study site to calculate the benefits of control. In addition to valuing the direct services provided by the resources that are traded in the market (in this case water provision), a contingent valuation study was undertaken in Abbottsford and Dorchester Heights (two suburbs in East London banking the Nahoon River). These were done in order to assess any non-use value a sample of 132 households of the population has for the control of water hyacinth, and any use values that are not traded in the market, for example recreational value. When the benefits of control of water hyacinth were compared to the costs of one of the least cost effective methods of control (herbicidal control), the benefits outweighed the costs by a ratio of more than 4:1, and for the most cost effective method of control the ratio was almost 6:1. These results provide a justification for the funds that are devoted to the control of water hyacinth, providing an argument for the continued expenditure for its control, and for further research into more cost effective methods of control, such as biological control.
Keywords: Water hyacinth -- Control -- South Africa; Urban ecology (Sociology) -- South Africa; Biodiversity -- Economic aspects -- South Africa; Biodiversity conservation -- Economic aspects -- South Africa; Biological invasions -- Economic aspects -- South Africa; Biological invasions -- Environmental aspects -- South Africa